Existence and Uniqueness of the Solution of Lorentz-Rössler Systems with Random Perturbations. (4th April 2013) - Wang, Xiaoying; Jiang, Fei; Yin, Junping
Abstract : We consider a new chaotic system based on merging two well-known systems (the Lorentz and Rössler systems). Meanwhile, taking into account the effect of environmental noise, we incorporate whit-enoise in each equation. We prove the existence, uniqueness, and the moments estimations of the Lorentz-Rössler systems. Numerical experiments show the applications of our systems and illustrate the results.